2008
DOI: 10.1080/13607860801987238
|View full text |Cite
|
Sign up to set email alerts
|

Screening for depression and assessing change in severity of depression. Is the Geriatric Depression Scale (30-, 15- and 8-item versions) useful for both purposes in nursing home patients?

Abstract: The objectives of this study were to determine the ability of the 30-, 15-and 8-item versions of the GDS for screening and assessing change in severity of depression in nursing home patients. The GDS and the MADRS were administered to 350 elderly NH-patients by trained interviewers. The presence of major (MaD) or minor depression (MinD) was evaluated with the Schedules for Clinical Assessment in Neuropsychiatry. Receiver Operator Characteristic (ROC) curves of the GDS-versions were performed to measure the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
0
41
1
Order By: Relevance
“…The internal consistency of the MADRS (a ¼ 0.68) was acceptable, indicating that the items of the MADRS reflect depressive symptoms in a healthy study population reasonably well. Three other studies on the internal consistency of the MADRS showed inconsistent results in different study populations (Table 4) (Hammond, 1998;Suzuki et al, 2005;Smalbrugge et al, 2008). The Cronbach's alpha of 0.41 for the GDS-15 in our study is low, which might be attributed to the strongly skewed distribution and the small variance, probably due to the yes/no answer format.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The internal consistency of the MADRS (a ¼ 0.68) was acceptable, indicating that the items of the MADRS reflect depressive symptoms in a healthy study population reasonably well. Three other studies on the internal consistency of the MADRS showed inconsistent results in different study populations (Table 4) (Hammond, 1998;Suzuki et al, 2005;Smalbrugge et al, 2008). The Cronbach's alpha of 0.41 for the GDS-15 in our study is low, which might be attributed to the strongly skewed distribution and the small variance, probably due to the yes/no answer format.…”
Section: Discussioncontrasting
confidence: 69%
“…The Cronbach's alpha of 0.41 for the GDS-15 in our study is low, which might be attributed to the strongly skewed distribution and the small variance, probably due to the yes/no answer format. Other studies reported better results in various study populations with a higher number of depressed subjects (Table 4) (Yesavage et al, 1982;D'Ath et al, 1994;Jongenelis et al, 2005;Batistoni et al, 2007;Smalbrugge et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The GDS has 30 items and each one was coded as 0 (no) or 1 (yes). The GDS has been used in numerous studies on geriatric depression both domestic and overseas, and its reliability and validity are excellent (Yesavage et al, 1983;Chau et al, 2006;Chan, 1996;Debruyne et al, 2009;Smalbruge et al, 2008). In this study, participants with a GDS total score of 11 or above were classified as depressed.…”
Section: Instrumentsmentioning
confidence: 98%
“…The GDS has been utilized in LTC institutions in many countries (Jongenelis et al, 2005;Smalbrugge, Jongenelis, Pot, Beekman, & Eefsting, 2008). It is easy to administer and could play a role in detection at a lower cut-point, especially in residential care and assisted living settings that may have already adopted its use (Watson & Coben, 2009).…”
Section: Introductionmentioning
confidence: 98%